Szempontok az irányítási rendszer modellváltásához - Faragó, László (Tér és Társadalom, 1991)
According to the author, during the three decades following the Second World War, the highly successful control model of the developed capitalist countries shows several similarities to the socialist experiment which failed. Central control and planning became the bureaucratic means of realizing central objectives and direct intervention into market mechanisms. This model was also built up of the basic elements of the economy and it also focused on economic development. This stystem gave preferences to large, productive organizations. National economy was considered to be the most relevant level of planning, and state intervention was a generally accepted doctrine. The main purpose was, everywhere, to develop a uniform industrial society, and thus specific regional interests could not be taken into account. By the 1980s, as a result of the new industral revolution, this "success model" of modernization lost some of its driving force, and the developed Western states, parallel with Central-Eastern Europe, are looking for the new structure which could/would give new impetus to development. With the analysis of the spatio-cultural existence of people, and of the local dependencies, the author intends to support the idea, that the tendencies of decentralization which started all over the world, and the increased role of small communities, the locality, have very deep roots. People try to find their safety in the center of their spatial relations, in their everyday Lebensraum. The importance of those small territories, where people can communicate face to face, where everybody can react to, and if necessary, can influence the processes, is continuously growing. Developments are increasingly based on regional identity formed by the actors of the region and rooted in local culture. Actors of everyday life are dependent on regionally reproduced socio-economic conditions. The traditional and modern forms of local dependencies decrease the willingness of people and organizations to change and mobility and, at the same time, arm them to carry out activities required to enforce their own interests. Development is a kind of structural change, when economic, cultural, political, ecological and other factors influence each other in a new way, thus it cannot be identified with quantitative development. Wording and executing the aims related to the "soft" characteristics of development (quality of life, preservation of cultural heritage, self-government, political independence, quality of environment, etc.) can only partly be imagined on national level, and the different regions and settlements have significant role in them, too. Requirements of local economic development (exploring specific conditions and using them to the greatest excent in local interests, etc.) also necessitate a model which is constructed from the bottom to the top. The author describes the theoretical outlines of a regional-centric control/planning model, where the different economic activities, consumption, quality of life, etc. are equally judged and considered, and which can be reconciliated with the political and economic changes and does not interfere with the model of local governments to be introduced soon, either. In this model, the state is not the most important determining factor any more. The regionally separated population is the basic principle of organization/arrangement. The space separates, makes the regional interests more articulate and solid, but at the same time it is also dissolved, because it is the basic interest of separate regional/spatial units to find the ways of cooperation, which – in the majority of cases – can be found in horizontal relations. Based on mutually acknowledged similarity of interests, the different regional units can plan common programs and/or coordinate their acitivities. Central control has normative influence on local control and planning. Direct interventions are only accidental. It is very useful, if the central authorities and state organizatons participate in the support of issues preferred on the basis of agreements and according to the guarantees of legal contracts. Planning is becoming political, and regional movements have increasing role in them. Finally, the author draws the conclusion, that Hungary should not follow mechanically the course of modern development dictated by the West mechanically, but we do not need the preservation of our ancient, cultural achievements either. What we really need is a path of development, which helps everybody in preserving his/her own, communal and national identity and sustains the environmental balance. We should choose the course of development, which would facilitate us to accept and receive the values of the diversity of cultures without becoming the victims of "the imperialism of cultural policy" and without making our system of preferences totally international. The development strategy which is built up from the bottom to the top, tolerates differences and is in harmony with nature – this would substitute the development policies based on one doctrine and central development policy – does not necessarily mean a "specific Hungarian way". At present, there are several development theories/strategies which promise more equitable and more balanced regional development, and which have already been and are still applied successfully in several countries. During more than one thousand years of her history, Hungary should try, for the first time, to develop a new course of development built up from the bottom to the top, and this way we could go by the latest trends of development.